Cloning and Expression Analysis of the Heat-Shock Protein 70 Gene in Eogystia hippophaecolus (Lepidoptera: Cossidae). (30th June 2017) - Wenbo, Li; Mingming, Cui; Ping, Hu; Jing, Tao; Shixiang, Zong
Abstract: Eogystia hippophaecolus is a major borer pest of sea buckthorn in China, damaging the environment and sea buckthorn industry. It is widely distributed in the Three-North region of China, and its larvae are resistant to low temperatures. Because heat-shock protein 70 can repair misfolded proteins under low temperatures, thus preventing cell damage and improving tolerance, we investigated the adaptation of E. hippophaecolus HSP70. We screened the transcriptome of E. hippophaecolus for HSP70 homologs, identified a full-length gene, and cloned to obtain the open reading frame, which was 1896 bp in length and encoded 631 amino acids, with a molecular weight of 69.7 kDa. The amino acid sequence contained three signature sequences of the HSP70 family and a C-terminal cytoplasmic character sequence. A phylogenic tree demonstrated that EhHSP70 has high homology with HSP70 genes from other insect species. We measure expression of the HSP70 gene across tissues when larvae of E. hippophaecolus were cold shocked. We also measured expression during cold shock recovery. EhHSP70 expression varied across tissues at 25 °C, with the highest expression in the midgut. Compared with the control, the expression of EhHSP70 in the cuticle was fourfold higher after a cold shock of − 5 °C for 1 h. EhHSP70 expression was also significantly increased during the 1-h period following recovery from cold shock, then decreased. In summary, cold shock promoted the expression of EhHSP70, which may play an important role in the adaptation mechanism of cold tolerance in E . hippophaecolus larvae.